Asia-Pacific Security: Policy Challenges - W. Lovell, David (ANU Press, 2013)
Since September 11, 2001, our newspapers have been filled with the 'war on terror'; our governments have mobilised their resources for 'homeland security'; and people everywhere are braced for more terrorist attacks. Yet while the new threat is genuine, we must not lose sight of the continuing security concerns in the Asia-Pacific. Tensions persist on the Korean peninsula, in the Taiwan Straits and the South China Sea, and in Kashmir. The region is well supplied with weapons of mass destruction and may face an arms race, and there are a range of pressing human security issues. Likewise, the strategic realities of the region remain linked with US power, and with the emergence of China as a key regional player. The book examines the developing strategic relationships in the region, and clarifies the dilemmas for Australian policy-makers as they try to balance genuine engagement with the region against a long-standing and valued alliance with the United States. Emerging from discussions between the Shanghai Institute for International Studies and the University of New South Wales at ADFA, Asia-Pacific Security has a particular relevance for foreign-policy professionals and scholars of the region.